Lexical Ambiguity in The Movie Ford V Ferrari (2019) By James Mangold : a Semantics Study - Muhammad Hikmal Fadilla; Ervina CM Simatupang (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study investigates the phenomenon of lexical ambiguity in the film Ford v Ferrari (2019) through the lens of semantics. Lexical ambiguity, which occurs when a single word have more than one meaning, plays a significant role in both everyday communication and cinematic dialogues. The research aims to identify the types of lexical ambiguity found in the movie and analyze the meanings conveyed through those ambiguities. This study employs a qualitative descriptive method. The data were collected through several techniques, including watching the movie repeatedly, transcribing selected dialogues, identifying ambiguous words or utterances, and note-taking. By applying the theories semantics from George Yule (2010), Hurford et al. (2007), and Leech (1981). The data analysis technique involves classifying the ambiguous expressions into types of lexical ambiguity (polysemy and homonymy) and interpreting their meanings based on contextual usage, particularly affective and connotative meanings. To assure data validity, the researcher used theoretical triangulation, which involves comparing several semantic theories and rechecking the data to preserve consistency and accuracy. By highlighting how language ambiguity functions within the film's context, this study contributes to the broader understanding of semantics in audiovisual media and underlines the significance of interpreting meaning in cinematic discourse.